The Influence Of Organizational Culture And Work Environment On Employee Work Productivity At The Animal Husbandry And Animal Health Service Of Lampung Province - Prayoga, Lutfi Arya Hadi; Reniza Helena Putri (Jurnal Ekonomi, 2024)
DISNAKKESWAN Lampung Province faces employee productivity challenges such as lack of control and supervision, including tardiness issues. A less than optimal work environment, such as limited space and facilities, also hampers productivity. In addition, weak organizational culture and the inability to match work demands with employee needs also interfere with performance. The study aims to examine more deeply about these two factors whether they can increase employee productivity. The target of the respondents is employees of the Lampung Province Livestock and Animal Health Service (DISNAKKESWAN). 50 employees were used as a sample for this study. Saturated samples are used as a sampling technique. Using primary data obtained by distributing questions directly using paper whose number is in accordance with the number of questions to be answered and the number of respondents. SPSS 26 is used as a data processing application. The results of linear regression showed that the dependent variable had a positive role in the independent variable. Hypothesis analysis shows that organizational culture and work environment are very supportive of work productivity. Then simultaneously the two independent variables have an impact on the bound variable. Although this research still has some limitations, the author hopes that the results of this research can be a useful guide in the future, so that employees can be more optimal in their work and are expected to increase employee productivity.